Khoirun Nisa' Pengembangan Sumber Daya Manusia dengan Pemanfaatan Potensi dan Pemeliharaan Sarana Prasarana Desa Pait Kecamatan Kasembon Kabupaten Malang - Khoirun Nisa', Khoirun; Amelia, Ratih; Kurniawan, Ahmad (Universitas Negeri Surabaya, 2023)
for students to learn and understand the characteristics of life in society, so that students can play a role and participate actively in society. The goal Students can help solve problems in the community by being able to develop village potential and handle problems in the village and can complete coursework on campus. This KKNT program is equivalent to 20 credits. KKNT itself consists of various themes, one of which is village projects. Village project KKNT activities are an effort to empower village potential as much as possible to improve the welfare of village communities. Through the KKNT village project theme, it is hoped that villages with all their potential can be fully utilized through various new innovations, both in terms of natural resources and human resources. During the KKNT, students will make maximum contributions with the many activities carried out by students towards the community. Students are required to make a KKN report which contains activities, information and descriptions as well as work programs in terms of aspects of planning, implementation and the results of activities that have been achieved. The implementation method is divided into four areas, namely physical infrastructure, increased production, social culture and health. From this method, a solution is produced, namely a superior work program.